Anthelmintic activity of plant extracts from Brazilian savanna - Oliveira, Andreia F.; Costa Junior, Livio M.; Lima, Aldilene S.; Silva, Carolina R.; Ribeiro, Maria N.S.; Mesquista, José W.C.; Rocha, Cláudia Q.; Tangerina, Marcelo M.P. [UNESP]; Vilegas, Wagner [UNESP] (Elsevier, 2017)
Helminth infections represent a serious problem for the production of small ruminants that is currently aggravated by resistance to anthelmintic products and has induced a search for control alternatives, such as natural products. In this study, extracts of Turnera ulmifolia L. (leaves and roots), Parkia platycephala Benth. (leaves and seeds) and Dimorphandra gardneriana Tul. (leaves and bark), which have been cited in ethnoveterinary studies and selected naturally by goats in the cerrado (Brazilian savanna), were tested in vitro against Haemonchus contortus. Hydroacetonic (ACT) and hydroalcoholic (ETH) extracts were evaluated using an Egg Hatching Assay (EHA), a Larval Exsheathment Inhibition Assay (LEIA) and a Larval Development Assay (LDA). A second set of incubations was performed using polyvinylpolypyrrolidone (PVPP) to determine the influence of polyphenols on the anthelmintic effects of EHA and LEIA. Data from each extract were used to calculate inhibition concentrations (IC50). All tested extracts showed activity against at least one life stage of H. contortus. The use of PVPP revealed that the tannins are not the only extracts of secondary metabolites responsible for the anthelmintic effects. The results showed clear in vitro anthelmintic activities against H. contortus at different stages and indicated the potential use of these species as a promising alternative approach to control helminthic infections of small ruminants.
Keywords: Haemonchus contortus; Natural product; Small ruminant